2001
DOI: 10.1590/s1517-83822001000300010
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of Proteases From Streptomyces Clavuligerus Using an Inexpensive Medium

Abstract: The partial characterization of extracellular proteases from Streptomyces clavuligerus NRRL 3585 and 644 mutant was investigated. The enzyme production was carried out in batch fermentation using soy bean filtrate as nitrogen source. Maximum activity was obtained after 96h of fermentation with an initial pH of 7.0. The enzyme was partially purified by ammonium sulphate precipitation. Enzymes from the two strains retained 37% of their initial activities at pH 8.0 after 2 h incubation at 25ºC. Enzyme half-life a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
5
7
1
1
Order By: Relevance
“…1). This result is in agreement with Bascaran et al, (3) and Moreira et al, (25), who showed that synthesis of protease from Streptomyces clavuligerus starts in the early stationary phase of growth. Similarly, in Streptomyces rimosus, the optimum protease production was recorded at 166 h (36).…”
Section: Resultssupporting
confidence: 93%
“…1). This result is in agreement with Bascaran et al, (3) and Moreira et al, (25), who showed that synthesis of protease from Streptomyces clavuligerus starts in the early stationary phase of growth. Similarly, in Streptomyces rimosus, the optimum protease production was recorded at 166 h (36).…”
Section: Resultssupporting
confidence: 93%
“…The results show that the optimum cultivation periods for milk-clotting enzyme productions were 56 h (M1) and 48 h (M2). These results are in agreement with those of other authors (Porto et al 1996;Moreira et al 2001), which showed that protease synthesis starts in Streptomyces clavuligerus in the post-exponential phase of growth. A higher production of milk-clotting enzymes between 72 and 192 h of growth has been reported for P. oxalicum, M. baciliformis and Mucor miehei (Areces et al 1992;Escobar & Barnett 1993;Hashem 1999).…”
Section: Effect Of Culture Time On Protease and Milk-clotting Enzyme supporting
confidence: 94%
“…The proteolytic activity was determined as described previously (Moreira et al 2001), in cell-free supernatants clarified by centrifugation (12,000 · g) for 5 min at 25°C. Azocasein, 1.0% (w/v) (Sigma Chemical Co., St. Louis, Mo USA) in 0.1 M Tris-HCl, pH 7.6, containing 1 mM CaCl 2 , was used as substrate.…”
Section: Enzyme Assaymentioning
confidence: 99%
“…The ability to digest casein was demonstrated by the formation of transparent halos on the plates and expressed in millimeter. Positive strains were submitted to the quantitative test described by Moreira et al [8]. The proteolytic activity was determined in the cell-free supernatants obtained by centrifugation (5,500×g) for 5 min at 25°C.…”
Section: Screening Of Proteolytic Yeastsmentioning
confidence: 99%